Value belief norm approach for determining picking up litter behaviour among visitors at Penang National Park, Malaysia - Ajuhari, Zamru (2016)
This study looks for an indirect management tool that can address the issue of visitors’ depreciative behaviour at Penang National Park (PNP). Specifically,this study is objectify at determining visitors’ salient beliefs, modal salient beliefs, and most important beliefs as measured through environmental beliefs(Awareness of consequences -AC, Environmental concenrn -EC, and Ascribed responsibility -AR) as outlined in Value Belief Norm Theory for the use of persuasive communication to encourage litter pick up thus redusing the amount of litter in the park. To answer the research questions and objectives,this study was divided to two phases: beliefs elicitation study and beliefs measurement phase. For both phases, litter were placed on the trail and visitors were observed by either picking up or not picking up the litter that has been placed earlier as they encountered onsite.Result from content analysis for belief elicitation study shows that there were a total of 41 salient beliefs were elicited with the frequency of 175 for compliers and 156 for non-compliers. Furthermore, a total of 20 modal salient beliefs have been determined and carried out to the next phase of the study. For the second phase of the study, 20 modal salient beliefs were carried out including 8 items measuring personal norm (PN) into the fix-item questions by asking visitors to rate their agreement on each item in EC, AC, AR and PN to the scale of 1 to 5 (1 being strongly disagree while 5 being strongly agree). For that purpose, a total of 276 visitors were systematically random sampled consisted of 138 compliers and 138 non-compliers.Findings reveal that all beliefs (EC, AC and AR) were positively correlated to PN with EC (r=.81, p=.01) was highly positively correlated to PN as compared to AC (r=.73, p=.01) and AR (r=.62, p=.01). Moreover, multiple regression equation (r2=.69, p=.01) showed that EC (B=.61, p=.01) had the most influence on PN as match up against AC B=.19,p=.02) and AR (B=.26, p=.01). Based on the result, it can be assumed that persuasive messages that is intended to encourage visitor to pick litter in PNP can be enhanced through EC-beliefs spectrum. Therefore, independent t-test was conducted to determine beliefs with persuasion potential by distinguishing EC beliefs for both groups. Based on the analysis, there were two EC beliefs with persuasion potential: ‚I am concerned about the environmental problem that litter may bring because of the consequences for the plants and wild animals in the park‛ (M=4.40, SD=.84)and ‚I’m concerned about the environmental problem that litter may bring because of the consequences for the next generations‛ (M=4.56, SD=.71). Based on the finding, it could be useful for PNP to consider both of the beliefs above for persuasive communication intervention such as persuasive signage at PNP to reduce the amount of litter in the park. This paper adds to growing body of literature informing the use of theory-driven approaches to influence the leisure behaviour in the protected areas.